2005
DOI: 10.1128/aac.49.4.1529-1541.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofccaR, Encoding the Positive Activator of Cephamycin C and Clavulanic Acid Production inStreptomyces clavuligerus, Is Dependent onbldG

Abstract: In Streptomyces coelicolor, bldG encodes a putative anti-anti-sigma factor that regulates both aerial hypha formation and antibiotic production, and a downstream transcriptionally linked open reading frame (orf3) encodes a putative anti-sigma factor protein. A cloned DNA fragment from Streptomyces clavuligerus contained an open reading frame that encoded a protein showing 92% identity to the S. coelicolor BldG protein and 91% identity to the BldG ortholog in Streptomyces avermitilis. Sequencing of the region d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 53 publications
(71 reference statements)
1
40
0
2
Order By: Relevance
“…Although an understanding of the higher level regulatory system that controls the expression of pathway-specific regulatory genes for individual biosynthetic gene clusters should be essential to control and improve the secondary metabolite production, only a few cases have been studied to date (9,10,20). The results with the bdpA disruptants of S. avermitilis suggest that the BdpA protein, which is an AdpA homolog, has the ability to activate the expression of strR.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although an understanding of the higher level regulatory system that controls the expression of pathway-specific regulatory genes for individual biosynthetic gene clusters should be essential to control and improve the secondary metabolite production, only a few cases have been studied to date (9,10,20). The results with the bdpA disruptants of S. avermitilis suggest that the BdpA protein, which is an AdpA homolog, has the ability to activate the expression of strR.…”
Section: Discussionmentioning
confidence: 73%
“…4), thereby confirming the role of CcaR in the regulation of cephamycin C biosynthesis in recombinant S. avermitilis. It has also been reported that the expression of ccaR in S. clavuligerus was dependent on the anti-sigma factor antagonist encoded by bldG (20). It was, therefore, of some interest whether or not the corresponding bldG ortholog in S. avermitilis, rsbV (sav4614), could control the expression of ccaR.…”
Section: Heterologeous Expression Of Exogenous Gene Clusters For Secomentioning
confidence: 99%
“…A bldG probe was included as an internal control in every reaction; that for claR (shown in Fig. 7c) was repeated without the bldG probe to allow visualization of the claR-tsp2 protected fragment, which differs from that of the bldG-tsp1 protected segment by only one nucleotide (Bignell et al, 2005). Reactions for each strain were performed concomitantly, loaded on the same gel and exposed on the same film, allowing quantitative comparison of different time points and different strains for each probe.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel, transcription of the regulatory genes ccaR (Pérez-Llarena et al, 1997) and bldG (Bignell et al, 2005) (both involved in the regulation of cephamycin C and clavulanic acid production), and of claR (Pérez-Redondo et al, 1998, Paradkar & Jensen, 1998 (involved in regulating clavulanic acid biosynthesis), was determined, as was that of relA.…”
Section: Characteristics Of the S Clavuligerus Rela-null Mutants Andmentioning
confidence: 99%
“…To complement the DSCAB1401 mutant, a~1.7 kb fragment containing the SCAB1401 coding sequence and 1 kb of upstream DNA was amplified by PCR and cloned into the EcoRI site of the QC31 integrative plasmid, pAU3-45 (Bignell et al, 2005). The resulting plasmid, pRFSRL34, was moved to the DSCAB1401 strain by conjugation.…”
Section: Methodsmentioning
confidence: 99%